P381 Infliximab induction regimes in steroid refractory acute severe colitis: a multi-centre retrospective cohort study with propensity score analysis. (25th January 2019) - Sebastian, S; Myers, S; Syed, N; Argyriou, K; Martin, G; Los, L; Fiske, J; Ranjan, R; Cooper, B; Patel, N; Goodoory, V; Shaikh, F; et al.
Abstract: Background: While infliximab is used as rescue therapy for steroid refractory acute severe colitis (ASUC), between 30 and 40% of patients do not respond and undergo colectomy. Accelerated induction regimes of infliximab have been proposed to improve response rates. We aimed to evaluate colectomy rates in steroid refractory ASUC patients receiving standard induction (SI) vs. accelerated induction (AI) of infliximab. Methods: Data collected on hospitalised patients receiving rescue therapy for steroid refractory ASUC. The choice of rescue therapy was at the discretion of the treating clinician. Accelerated induction (AI) was defined as receiving second dose of infliximab within 8 days of first rescue therapy or receiving front loading dose of 10 mg/kg. Our primary outcome was the short-term (in-patient, 30 days and 90 days) colectomy rate. Secondary outcomes were 12-month colectomy rates, length of hospital stay (LOS), and complication rates. We used a propensity score analysis with optimal calliper matching using a priori defined high-risk covariates at the start of rescue therapy (albumin, CRP, CRP–albumin ratio, haemoglobin nadir and pancolitis) to reduce potential provider selection bias. Results: A total of 131 patients receiving infliximab rescue therapy were included, of whom 102 patients received SI and 29 received AI. There was no difference in age, duration of diagnosis, age at rescue therapy, Montreal class or use of steroids, 5ASAs or thiopurines prior to index admission. In the unmatched overall cohort, there was no difference in colectomy during index admission (13% vs. 20%, p = 0.26), 30-day colectomy (18% vs. 20%, p = 0.45), 90-day colectomy (20% vs. 24%, p = 0.38) or 6 month colectomy (25% vs. 27%, p = 0.49). The LOS was shorter in the SI group (14.87 ± 8.1 days vs. 19.31 ± 5.8 days, p = 0.007). In patients who underwent colectomy, there were no differences in complications or serious infection rates. In the propensity score-matched cohort of 52 patients, there was no difference in overall colectomy rates between SI and AI groups (57% vs. 31%, p = 0.09), but the index admission colectomy (53% vs. 23%, p = 0.045) and 30-day colectomy (57% vs. 27%, p = 0.048) rates were higher in those receiving SI. There was no significant difference in LOS between SI and AI groups (23.6 ± 4.3 vs. 18.2 ± 7.1 days, p = 0.09) or in overall complication and infection rates but there was a mortality in AI group. Conclusions: In this retrospective cohort study, there was no difference in overall colectomy rates in ASUC patients receiving different induction dosing regimens of infliximab. However, using propensity score matching, the short-term colectomy rates appear to be better in those receiving accelerated induction regime. A prospective study to confirm findings is planned.